Steel lattice tower under ultimate load - chosen joint analysis = Stalowa wieża kratowa pod obciążeniem niszczącym - analiza wybranego węzła - Szafran, Jacek; Rykaluk, Kazimierz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The main objective of the presented paper is to discuss chosen lattice tower joint behavior under structure ultimate load. Joint numerical modelling considerations are enriched with comparison to the full-scale tower pushover test results.
Keywords: steel latticed towers; l-section; finite element analysis; structural joint; fullscale test; eccentricity of load; stalowe wieże kratowe; kątownik stalowy; metoda elementów skończonych; połączenia; testy konstrukcji; mimośród obciążenia